2023
DOI: 10.1080/07853890.2023.2242781
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, characteristics and measurement of somatic symptoms related to mental health in medical students: a scoping review

Abstract: Introduction Somatic symptoms related to mental health in medical students are under-researched, with nothing on the topic being published in the United States in over three decades. This scoping review is the first of its kind to explore the prevalence, type and severity of somatic symptoms induced by stress, anxiety, depression and burnout amongst medical students, with the objective of describing the significance and breadth of this issue. Methods PRISMA-ScR guidelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 98 publications
0
3
0
Order By: Relevance
“…In the present study, resilience factors associated with lower levels of somatization symptoms among dental and nursing students included emotional balance and self-awareness (34.44%). This aligns with findings from Sperling et al (2023) [66], who highlighted the importance of emotional regulation and self-awareness in reducing somatic symptoms among medical students. Similarly, another research indicated that self-reflection and emotional self-disclosure contribute significantly to post-traumatic growth in nursing students, reporting on the role of self-awareness in mental health resilience [67].…”
Section: Resilience Factors For Dentistry and Nursing Studentssupporting
confidence: 88%
See 1 more Smart Citation
“…In the present study, resilience factors associated with lower levels of somatization symptoms among dental and nursing students included emotional balance and self-awareness (34.44%). This aligns with findings from Sperling et al (2023) [66], who highlighted the importance of emotional regulation and self-awareness in reducing somatic symptoms among medical students. Similarly, another research indicated that self-reflection and emotional self-disclosure contribute significantly to post-traumatic growth in nursing students, reporting on the role of self-awareness in mental health resilience [67].…”
Section: Resilience Factors For Dentistry and Nursing Studentssupporting
confidence: 88%
“…Somatization of stress refers to the phenomenon where psychological distress manifests as physical symptoms without discernible organic pathology (Feussner et al, 2022) [9]. This is particularly concerning in healthcare education due to the demanding nature of these disciplines and the potential implications for students' future clinical practice (Sperling et al, 2023) [10]. Among dental students, who face significant stressors during their education, somatization symptoms such as tension-type headaches with a positive association with painful TMD or bruxism are prevalent, linking these symptoms to stress and psychological functioning (Câmara-Souza et al, 2020) [11].…”
Section: Introductionmentioning
confidence: 99%
“…In some other studies, in similarity with ours, patients with headache and/or bodily pain were investigated for psychiatric symptoms with various questionnaires (9,5,12,13,14).…”
Section: Discussionmentioning
confidence: 81%
“…Back pain, neck pain. Hheadaches, sleep disturbances, and functional gastrointestinal disorders were examples of somatic symptoms (13).…”
Section: Discussionmentioning
confidence: 99%
“…Stress predicts somatic symptoms in students under academic stress ( 29 ). The prevalence of somatic symptoms ranged from 5.7 to 80.1%, and somatic symptoms were overwhelmingly found to be significantly correlated with mental ill-health ( 30 ). A previous study has shown that physical reactions may be one of the most symptoms of learning stress during the COVID-19 pandemic ( 31 ).…”
Section: Discussionmentioning
confidence: 99%